Dependence of tissue inhomogeneity correction factors on nominal photon beam energy. (September 2016) - Akhtaruzzaman, M.; Kukolowicz, P.
Abstract : Introduction: Before the first clinical use of the treatment planning system commissioning of dose calculation algorithms must be performed. One of the most difficult tasks is to check the accuracy of calculations in the inhomogeneous absorber. Several results of so called inhomogeneity correction factors were published but it is not clear, if they might be used for the user beam due to differences in beam energies. Purpose: The aim of the study was to check how much the correction factors depend on the energy of the beam. Materials and methods: The Batho correction method, which is the ratio of powers of Tissue Air Ratios (TARs), was used for calculation of the set of correction factors for lung. The TAR factors for wide range of energies were calculated using depth doses with the Gerbi's formula (Gerbi, Med. Phys.18(4), 724, 1991) and peak scatter factors with the Li's formula (Allen Li, Med. Phys. 26(6), 962, 1999). The correction factors were calculated for lung of 0.25 g/cm 3 density for several beam sizes and points lying at several depths inside of and below lung. Results: The linear dependence of the correction factors on the energy were obtained. For nominal energies of 6 MV (TPR20/20 = 0.670) and 15 MV (TPR20/20 = 0.750), the 1% difference in energy lead to changes of CF of 0.7% and 0.8% respectively inside of lung. The maximum differences for points below lung were 1%. Conclusion: For two photon beams of energies differed no more than 1%, the correction factors differ of less than 0.8%.